A South Korean Village Movement Towards Abatement of Malaria in Sub‐Saharan Africa: A Policy Design for Experimentation in Uganda. Issue 1 (18th August 2017) - Okwir, Martin
Abstract : The Nations in Sub‐Saharan Africa, including Uganda, have been suffering from malaria epidemics from time immemorial. Not only have the malaria epidemics been claiming countless lives but it also has been depressing labor productivity. To deal with this devastating epidemic the modern Ugandan government and International Organizations have been mobilizing the government agencies to fight malaria. These efforts, however, have not been successful as policymakers expected. The present study proposes an alternative approach to malaria abatement, which empowers the villagers themselves to fight malaria. The hypothesis is that if the villagers are properly motivated to fight for their own health and life, they will eradicate malaria epidemic more effectively and efficiently. The idea of local empowerment is a concept that has been successfully utilized in South Korea during her developmental stage in the 1970s to modernize the agricultural communities. The present study borrows key concepts from South Korea's "New Village Movement" and applies them to local efforts in Uganda. The purpose of this study was to take the first step to examine the feasibility of such an approach. It develops a policy design at the village level and examines the necessary costs and benefits in comparison to the top‐down approach. To achieve the study objectives, a desk review approach was adopted where data and the required information was obtained from studies and publications by World Bank, World Health Organizations and government sources. The study concludes that the current policy framework to fight malaria in Uganda has failed to achieve expected results in addition to it being expensive. The study concludes that a community based approach like that applied in South Korea ought to be adopted so as to achieve multiple objectives of fighting malaria, poverty reduction and accelerated economic growth. The approach is cost effective and requires running for a certain period of time.